2019
DOI: 10.1208/s12248-019-0351-9
|View full text |Cite
|
Sign up to set email alerts
|

A Pediatric Covariate Function for CYP3A-Mediated Midazolam Clearance Can Scale Clearance of Selected CYP3A Substrates in Children

Abstract: Recently a framework was presented to assess whether pediatric covariate models for clearance can be extrapolated between drugs sharing elimination pathways, based on extraction ratio, protein binding, and other drug properties. Here we evaluate when a pediatric covariate function for midazolam clearance can be used to scale clearance of other CYP3A substrates. A population PK model including a covariate function for clearance was developed for midazolam in children aged 1–17 years. Commonly used CYP3A substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 69 publications
(54 reference statements)
0
8
0
2
Order By: Relevance
“…Recently, a framework was published for between-drug extrapolation of covariate models 55 which was used by Brussee et al to study whether scaling with a pediatric covariate function from midazolam will lead to accurate clearance values of other CYP3A substrates. 56 Clearances of drugs were accurately scaled when they were mainly eliminated by CYP3A-mediated metabolism with, for example, high protein binding to albumin (> 90%) and a low-to-intermediate extraction ratio of < 0.55 in adults. However, the covariate relationship for clearance was based on data from children > 1 year of age.…”
Section: Articlementioning
confidence: 99%
“…Recently, a framework was published for between-drug extrapolation of covariate models 55 which was used by Brussee et al to study whether scaling with a pediatric covariate function from midazolam will lead to accurate clearance values of other CYP3A substrates. 56 Clearances of drugs were accurately scaled when they were mainly eliminated by CYP3A-mediated metabolism with, for example, high protein binding to albumin (> 90%) and a low-to-intermediate extraction ratio of < 0.55 in adults. However, the covariate relationship for clearance was based on data from children > 1 year of age.…”
Section: Articlementioning
confidence: 99%
“…On the other hand, there are few studies reported in the literature about clinical trials using a MDZ pediatric population model ( Brussee et al, 2019 , de Wildt et al, 2003 , van Groen et al, 2019 , Vet et al, 2016 , Völler et al, 2019 ), which have contributed to this type of population pharmacotherapy within the hospital environment.…”
Section: Resultsmentioning
confidence: 99%
“…Although the same CBZ formulation was administered at fix times, we cannot exclude potential additional variations in absorption associated with varying feeding times (child nourished ad libitum). While we accounted for expected increases in clearance and volume of distribution with weight by standard allometric scaling (with a close estimate of 0.874 proposed for the CYP3A4 reference drug midazolam 37 ) we cannot exclude additional or confounding age‐dependent changes.…”
Section: Discussionmentioning
confidence: 99%